Ludwig's angina complicating pregnancy: an unusual presentation - Singh, Aruna; Saha, Pradip Kumar; Kumar, Abhay; Bagga, Rashmi; Chauhan, Neha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Pregnancy is a state of several physiological changes, which predisposes many to oral health problems. However, the majority of pregnant women do not receive oral health counseling. Pregnant women who receive inadequate dental care are at risk for odontogenic infections, which can have serious consequences. Here we are presenting a case of 32 weeks pregnancy with Ludwig's angina complicated by acute renal failure.